THE RELATIONSHIP OF EARLY BREASTFEEDING INITIATION (IMD) TO POST PARTUM UTERINE INVOLUTION IN THE INDEPENDENT PRACTICE OF MIDWIVES (PMB) MARIYAH ULFAH EAST JAKARTA - Pratiwi, Meysa; Prastyoningsih, Aris; Umarianti, Tresia (Universitas Kusuma Husada Surakarta, 2025)
Early breastfeeding initiation (IMD) is one of the factors that influence uterine involution. IMD can stimulate and release hormones, including the hormone oxytocin, which functions in addition to stimulating contraction of breast smooth muscles, also causes contraction and retraction of uterine muscles. This will compress the blood vessels resulting in reduced blood supply to the uterus. In women who choose to breastfeed their babies, the baby's suction will stimulate the release of oxytocin and help the uterus return to its normal shape. This study aims to determine the relationship of Early Breastfeeding Initiation (IMD) to uterine involution in post partum at PMB Mariyah Ulfah East Jakarta which was conducted in May-August 2024. The type of research used in this study is quantitative research. This study used a Cross Sectional approach. The sample technique used in this study was total sampling of 30 people. The research instruments used were metline and observation sheet. The results of this study identified that there was a difference in TFU reduction in mothers who did , Early initiation of breastfeeding (IMD) and those who did not do IMD, so there was a relationship between Early Breastfeeding Initiation (IMD) to Uterine Involution during the nifaas period at PMB Mariyah Ulfah East Jakarta, where the p-value = 0.006 (0.006 <0.05)